Sandung as a Form of an Artistic Expression for The Kaharingan Hindu Community in Palangkaraya City - Paramarta, I Made; Lestari, Wahyu (Gorga : Jurnal Seni Rupa, 2025)
This research has problems related to understanding the form of brisket. Basically, Sandung is well known to the Kaharngan Hindu community in Palangkaraya City, however, the forms of Sandung are still rarely understood. It needs to be dissected and analyzed into writing so that in the future it can be understood by the wider community. The urgency of this research is to fill the gap in previous research with current facts in the field (das sein) regarding the correlation between the forms of Sandung presented in artistic expressions for the Hindu community in Palangkaraya city. This research aims to examine Sandung as an artistic expression for the Kaharngan Hindu community in Palangkaraya city. This research uses a qualitative method with a phenomenological approach using data collection techniques in the form of observation, interviews, documentation and literature review relevant to this research. This research uses A.A.M.'s aesthetic theory of Djelantik to dissect the shape of Sandung so that it can be studied in depth to create a complete and in-depth article about Sandung. The results of the research found that the shape, weight and appearance of the Sandung are very aesthetic. It is necessary to examine the actual shape and arrangement based on facts in the field, the atmosphere, ideas and messages conveyed through the shape of the Sandung, and what talents, skills, facilities and media are used. presented in the form of Sandung. Based on the results of the analysis, this research is expected to contribute knowledge in the form of Sandung to the Kaharngan Hindu community in the city of Palangkaraya.